Understanding Employee Acceptance of Algorithmic Leadership in Indonesia: Insights from Institutional Logic and Industry Type - Yusmedi Nurfaizal; Agapito Barros (Journal of Leadership in Organizations, 2026)
Introduction/Main Objectives: This study examines the impact of ethical decision-making by university leadership on academic freedom and institutional integrity in two Zimbabwean universities. Background/Problems: Empirical evidence on how ethical leadership in Zimbabwean higher education institutions manages the tension between academic freedom and institutional reputation remains limited. These challenges are intensified by limited resources, fragile governance frameworks, and significant government interference, which constrain institutional autonomy and complicate leadership decision-making. Novelty: This study introduces ethical leadership as a key analytical perspective for understanding the persistent yet understudied tension between academic freedom and institutional reputation in higher education institutions. Research Methods: A mixed-methods approach was used to explore ethical leadership in balancing academic freedom and institutional reputation. Qualitative data were collected through online interviews conducted via Zoom and Microsoft Teams with eight university leaders and twenty academics (four leaders and ten academics from each institution). In addition, a semi-structured questionnaire distributed through Google Forms gathered responses from 167 academics across the two universities. Finding/Results: The findings reveal substantial government interference affecting institutional decision-making, particularly in state universities. Foreign researchers working in Zimbabwean universities face greater restrictions than citizens and permanent residents. University leadership often prioritizes institutional reputation over academic freedom, limiting open communication and critical inquiry. The private university involved in the study also lacks formal policies protecting academic freedom. Conclusion: The study highlights the importance of ethical leadership and recommends clear ethical frameworks and leadership development programs to safeguard academic freedom while maintaining institutional integrity.